Philosophical Reflection of the Concept of "Borders" in Modern Culturechinese Performing - Ying, Du (2021)
Objective: philosophical reflection problems of the frontiers of science, knowledge and creativity in the modern intercultural integration; rationale for new interpretations and understanding of the concept "border" providing an integrative model for science and culture, which, in turn, implies the unacceptability of Orthodox approaches, and rigid demarcation between different spheres of cultural production. This explains the need to develop a "rational-reflexive culture" that meets the new demands of modern society. Research procedure and methods: the theoretical and methodological research of the work is based on the works of classics of Western and domestic philosophical, cultural, historical, and other thought in the field of studying the essence of social and cognitive phenomena; classical and non-classical methodological paradigms of understanding the concept of "borders" in ontological, epistemological grounds and socio-cultural dynamics are used. The main method is the classical method of dialectics, associated with the consideration of things in a broad ontological, epistemological and cultural-historical context; a method of comparative analysis, a combination of historical and logical, concrete-universal, phenomenological and systemic principles, a thesaurus approach. The results of the study: analyzed new meanings of the concept "border", "rational – reflexive culture" in knowledge and creativity; proven illegality model "narrow" technological oriented science and culture to the detriment of the spiritual nature of man; it is proved that as the modern world blurs the lines of demarcation in science, culture, art, insofar exacerbated the task of establishing priorities, implying the transition from a world of "pure rationality" to the life world of man; an optimal model of the conjugacy of all forms of human cognitive and creative activity in culture is proposed, due to the genetic connection of rational and other mental and cognitive forms of world development. Theoretical / practical significance consists in the justification and author's interpretation of the new understanding of the boundaries of science-culture-man; in proving the need to expand the boundaries of science in ontological and epistemological grounds to the "borders of culture"; implemented criticism of the technogenic interpretation of science (science as "sciepse"), with the connection with which the thesis is justified about the inexpediency of excessive rationalization of knowledge and cognition to the detriment of other ways and forms of world development.